Meaning from Juxtaposition: A Conversation with Photographer Jon Crispin about the Willard Asylum Suitcases. (25th April 2016) - Crispin, Jon; Crossland, Zoë
Abstract : An interview and accompanying photographic essay around Jon Crispin's photographs of a collection of abandoned suitcases found at a now-closed psychiatric center at Willard, in upstate New York. Many held the possessions of former patients and ranged in date from the turn of the 20th century into the late 1960s. The suitcases have now been accessioned to the permanent collection of the New York State Museum in Albany, NY.